Platelet Rich Plasma in Orthopaedics and Sports Medicine (Springer International Publishing, 2018)
This book provides a comprehensive, state-of-the art review of platelet rich plasmas (PRPs) in the field of regenerative medicine. The book begins with an overview of the basic science behind PRP, describing the role of platelets and growth factors followed by the most important biological effects expected from the use of PRPs. Platelet Rich Plasma in Orthopaedics, Sports Medicine and Maxillofacial surgery includes numerous contributions detailing the rapidly growing field of PRPs in clinical practice. From the origins in oral and maxillofacial surgery, to the latest advances in orthopaedics and sports medicine including the use of Platelet Rich Growth Factors (PRGF) in muscle, bone, tendon, ligament and nerve injuries among others. The volume concludes with contributions from experts in biology, orthopaedics, oral and maxillofacial surgery, where the convergence of expertise is leading to unprecedented insights into how to minutely control the in vivo fate and function of PRGF. This book will provide a useful resource for physicians and researchers interested in the rapidly changing field of biomedicine and learning more about this growing area of treatment. .